Cervical Length at 28–32 Weeks of Gestation Predicts Preterm Birth. Issue 3 (28th July 2021) - Zhang, Mengying; Zhang, Xiaoxiao; Yang, Huixia; Shi, Chunyan
Abstract: Objective: To evaluate the ability of cervical length (CL) at 28–32 weeks of gestation to predict spontaneous preterm delivery and preterm premature rupture of membranes (PPROM). Methods: It was a retrospective cohort study that vaginal ultrasonography at approximately 28–32 weeks of gestation was performed in 14, 953 women between 17–49 years old with singleton pregnancies who delivered after 28 weeks of gestation at the Peking University First Hospital from June 2008 to December 2012. The pregnancy outcomes were followed and the relationship between the CL and preterm delivery or PPROM was assessed. The relative risk was calculated to assess group differences in the likelihood of an event occurring. Results: The overall prevalence of preterm delivery was 5.7% (858/14, 953); the incidence for therapeutic preterm delivery was 2.1% (318/14, 953), for spontaneous preterm delivery was 0.9% (133/14, 953), and for PPROM was 2.7% (407/14, 953). Excluding the 318 women who had therapeutic preterm delivery, the relative risk of preterm delivery for women with a CL between 25 mm and <30 mm, between 15 mm and <25 mm, and <15 mm was 3.7, 9.3, and 30.2, respectively. The sensitivity, specificity, and positive and negative predictive values of CL ≤25 mm at 28–32 weeks of gestation as the cut-off value for predicting preterm delivery were 19.8%, 97.5%, 23.4%, and 96.9%, respectively. For preterm delivery before 35 weeks of gestation, the sensitivity, specificity, and positive and negative predictive values of a CL ≤ 25 mm at 28–32 weeks of gestation as the cut-off value were 30.0%, 97.2%, 11.8%, and 99.1%, respectively. In addition, women with PPROM ( n  = 407) had significantly shorter CL (31.9 ± 7.4) mm at 28–32 weeks of gestation compared that of women without PPROM (34.0 ± 8.3) mm. The incidence of PPROM in women with a CL≤25 mm at 28–32 weeks of gestation (19.4%, 79/407) was significantly lower than that for women with a CL >25 mm (80.6%, 328/407, P  < 0.05). Conclusion: CL at 28–32 weeks of gestation can predict spontaneous preterm delivery, and is valuable for predicting PPROM.